A Comprehensive Review on Traditional Knowledge, Phytochemistry and Pharmacological Properties of Acalypha indica L. - Ravi, Sahukari; Jyothi, Punabaka; Shanmugam, Bhasha; Subbaiah, Ganjikunta Venkata; Prasad, Singamala Hari; Reddy, Kesireddy Sathyavelu (Pharmacognosy Reviews)
Acalypha indica is a significant medicinal plant. The purpose of this review is to bring traditional usage, phytochemistry, and scientific applications of A. indica up to date. Microbial infections, fertility, stomach ulcers, snake bites, pains, wounds, liver/kidney problems, and rheumatism have all been traditionally treated with A. indica paste, decoction, sap, and synergy with other plants/plant products, which have all been scientifically proven through in vitro and in vivo experiments. Regardless of traditional knowledge, this plant extracts have been scientifically proven to help against cancer, inflammation, cardiac damage, diabetes, TB, and malaria. Phytochemical investigation revealed that A. indica has phenols, flavonoids, tannins, coumarins, alkaloids and their glycosides, saponins, volatiles and fatty acids. In summary, the presence of phytoconstituents is responsible for the A. indica traditional and pharmacological qualities. Further, conformational clinical trails in humans are necessary to ascertain the extracts efficacy. Extensive future studies are to be conducted to reveal the mechanism of action, pharmacokinetic properties and active phythochemicals of A. indica extracts.
Keywords: Acalypha indica; Phytochemicals; Pharmacological properties; Traditional uses; Medicinal plants